(untitled) (Journal of Economic Research & Business Administration, 2017)
In this work we were considered features of application of integrated marketing communications in the management of country brand. The authors analyzed the international experience of creating a national brand, the problem of creating an attractive brand and evaluation of country branding. It was drawn up by positioning the image of the world ranking of countries and made an analysis of the level of use of these countries integrated communications. Branding the country will contribute to the economic, social, cultural development of the country, most importantly contributes to the inflow of investment, which in many countries today is a source of livelihood, tourists, increase marketability of domestic products. The authors found that this requires the use of integrated marketing communications, the most advanced technology, to engage in the service sector of local entrepreneurs, thus providing a high level of employment and income.